Trajectory of Change in Erectile Dysfunction Symptoms Following Coronary Artery Bypass Surgery in Malaysian Population - Mohd Ali, Katijjahbe; Md Ali, Nur Ayub; Mohamed Sani, Suriati; Ismail, Muhammad Ishamuddin; Haron, Hairulfaizi; Azmi, Fahmi Pramaditto; Muhammad Nor, Mohamad Arif; Abdul Rahman, Mohd Ramzisham; Abdul Manaf, Mohd Rizal (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Despite the advantages of Coronary artery bypass surgery (CABG), this procedure has been reported to have a significant impact on sexual activity. The study aims to assess the trajectory of change in erectile dysfunction (ED) symptoms following CABG.METHODS: 73 adult male participants were recruited. Participant primary data was measured using the International Index of Erectile Dysfunction (IIEF-5) at three-time points. RESULTS: Severe ED was most prevalent during 6 weeks following-operation (86.3%); however, the proportion of severe ED symptoms reduced after 4 months following-operatively (42.5%). There was a statistically significant difference in ED symptoms between pre-operatively and 6 weeks post- operatively (p< 0.001). At 4 months, there was a marginally significant improvement in ED symptoms compared to baseline pre-operatively post CABG (p = 0.064). Age significantly increases the chance in odds of having abnormal ED symptoms by 22% at 4 months postoperatively (aOR=1.22, 95% CI=1.06, 1.41, p<0.05). Other risk factors for abnormal ED symptoms following CABG, which include normal creatinine clearance, being a smoker, and having moderate to good LV function was not statistically significant. CONCLUSION: The present study has demonstrated a high prevalence of ED following CABG and the procedure caused a negative impact on the ED symptoms. However, there was a significant improvement in ED symptoms as the time from surgery increases and patients recovered. Further studies with larger sample size and longer recovery time are needed to assess the trajectory of recovery in ED symptoms in this population.>< 0.05). Other risk factors for abnormal ED symptoms following CABG, which include normal creatinine clearance, being a smoker, and having moderate to good LV function was not statistically significant. CONCLUSION: The present study has demonstrated a high prevalence of ED following CABG and the procedure caused a negative impact on the ED symptoms.